(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2025)
Each city has utility values that make it attractive, including those that create tourist potential. The aim of the presented research was to assess the potential of Koszalin in terms of tourist assets. For the purposes of the article, a survey using a questionnaire was conducted. The study was conducted electronically via the Google Forms website. The study group consisted of full-time and part-time students of the Faculty of Economics of the Koszalin University of Technology. The questionnaire was created on November 19 and closed on December 11. A total of 69 correctly completed questionnaires were obtained. As a result of the conducted research, the research hypothesis was confirmed, according to which Koszalin has untapped potential in terms of tourist assets. Most attractions received quite high ratings – exceeding the average value of 4 on a five-point Likert scale. The highest ratings were given to the tourist trails on Chełmska Mountain and the Koszalin Aquapark. The knowledge of the respondents about the existence of individual attractions turned out to be varied, which indicates the need to promote the city’s assets. The most recognizable places are those for active recreation, especially the Koszalin Aquapark.